Role Model Student Facillitator And Explaning Pada Mata Pelajaran Fiqih - Qurotul Ayuni; Syamsul Arifin; Sri Wahyuni (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
SMA Al Maliki who has implemented the Student Facilitator and Explaning learning model, especially in fiqh subjects where the teacher applies the learning model through which students are made into groups first to discuss the material that has been prepared by the teacher, then students explain the results of the discussion in front of friends. peers in class. Through this learning model, students are expected to be active and increase their activeness in the learning process. The purposes of this study: 1) To find out the application of the Student Facilitator and Explaning Role Model in increasing student activity in fiqh subjects at MA Al Maliki in 2023. 2) To find out the results of the Student Facilitator and Explaning Role Model in increasing student activity in fiqh subjects in MA Al Maliki in 2023. This research uses a qualitative approach. Sources of data in this study consisted of two, namely: primary data and secondary data. This type of research is a case study. Observation data collection techniques, interviews. Data analysis used Miles and Huberman's interactive technique. The validity of the data used is source triangulation and technical triangulation. The results of this study are: 1) The Student Facilitator and Explaning Role Model in increasing student activity in fiqh subjects at MA Al Malik in 2022/2023 is for the teacher to make a Planning: Learning Implementation Plan (RPP) which includes competency standards, basic competencies, indicators , time allocation, learning methods, learning media, learning steps, learning resources, and evaluation. In the process of implementing the learning process, namely material about zakat, the teacher divides students into 4 groups consisting of 3 or 4 students and each group has a different material, namely about zakat. The evaluation used is a summative and formative evaluation in the form of a written test. 2) The results of the Student Facilitator and Explaning Role Model in Increasing Student Activity in the Subject of Fiqh at MA Al Maliki in 2022/2023 is that student activity is going well, students are quite enthusiastic and active in learning activities, both in terms of conveying material, this can This can be seen from the involvement of students during learning activities, such as speaking, delivering material/presentations, discussing, asking and answering questions